Failure analysis of the boiler water-wall tube. (October 2017) - Liu, S.W.; Wang, W.Z.; Liu, C.J.
Highlights: The failure of the boiler water-wall tube is investigated. The fire-facing side of the tube was observed to have experienced significant wall thinning. The iron-to-oxygen ratio of the fire-facing side is smaller than that of the back side. The failure occurred due to oxidation. Abstract: Failure analysis of the boiler water-wall tube is presented in this work. In order to examine the causes of failure, various techniques including visual inspection, chemical analysis, optical microscopy, scanning electron microscopy and energy dispersive spectroscopy were carried out. Tube wall thickness measurements were performed on the ruptured tube. The fire-facing side of the tube was observed to have experienced significant wall thinning. The composition of the matrix material of the tube meets the requirements of the relevant standards. Microscopic examinations showed that the spheroidization of pearlite is not very obvious. The failure mechanism is identified as a result of the significant localized wall thinning of the boiler water-wall tube due to oxidation.